BLACK TRAVEL WRITING : contemporary narratives of travel to africa by african american and black ... british authors. - Kalous, Isabel (TRANSCRIPT Verlag, 2021)
How did writers portray their journeys to Africa? What meanings were attached to the continent? And what was the role of travel writing as a means of self-exploration? To answer all these questions Isabel Kalous examines autobiographical travel narratives by African American and Black British authors published between the 1990s and 2010s. To provide a framework for the analyses of contemporary texts, she outlines the emergence, development, and key characteristics of the multifaceted genre of transnational Black travel writing. Authors discussed include, among others, Saidiya Hartman, Barack Obama, and Caryl Phillips.